Ants of Ambon Island - diversity survey and checklist - Latumahina, Fransina; Borovanska, Michaela; Musyafa; Sumardi; Putra, Nugroho Susetya; Janda, Milan (ZooKeys, 2015)
The present checklist of ants (Hymenoptera: Formicidae) of Ambon is the first comprehensive overview of ant species recorded on the island during the last 150 years. The species list is based on literature and museum collections' records combined with data from our field survey in 2010. In total, there are 74 ant species and subspecies representing 34 genera and six subfamilies known from Ambon. Five of the species found in undisturbed forest were exotic and indicate the overall habitat degradation on the island. The largest proportion of Ambon ant fauna are species with affinities to the Oriental region and species of Oriental-Austro-Melanesian origin. At least 20% of the species are regional endemics. In comparison to other islands in the region, the Ambon fauna seems more diverse and better sampled; however it is clear that a large part of it still remains to be described.
Keywords: Wallacea; Indo-Australia; biodiversity; habitat preferences; Moluccas; taxonomy; Indonesia; biogeography; invasive species; species distributions; Melanesia